Modeling of tidal current and residual currents patterns in Tomori Bay, North Morowali Regency, Central Sulawesi Province. Issue 1 (January 2021) - Sabhan,; Labania, H M D; Mudin, Y; Rahman, A
Abstract: Research has been carried out to model current patterns and residual current in Tomori Bay using Mohid Studio 2016. The model using a finite volume approach with a tidal model driven by the results of Geospatial Information Agency (BIG) predictions placed on the open boundary of the model. The modeling results are compared with the measurement results in Tomori Bay. The tidal current velocity in the high tide conditions increases the current velocity at the bay neck and weakens after passing Tokobae Island. The current velocity on the west side of Tokobae island is higher than that of the east of Tokobae. At the mouth of the bay, the current velocity on the north side is higher than at the south side of the bay mouth. The tidal current velocity is higher than the residual current with a maximum tidal current velocity of 25.3 cms −1 and a maximum velocity of residual current 12.6 cms −1 . The residual current that describes the fate of pollutants while in the Tomori Bay waters. The residual flow pattern shows a vortex on the north side of the bay mouth and to the southeast of Tokobae Island.